Response of Atriplex lentiformis to Management Practices on an Arid Salt Land - Arya, Ranjana; Gupta, G N; Kachhawaha, G R; Limba, N K (Annals of Arid Zone, 2016)
A rield experiment was conducted on an arid salt land to study the performance of A/riph:1: lClIlifonnis in response to different treatments such as gypsum. drainage. replacement of pit soil with good soil. FYM, nitrogen and zinc applications. Untreated bushes of A. lcmifonnis attained an average height of 99 cm. and crown diameter of 88 cm within 9 months of planting. Gypsum + drainage + urea + zinc applications (T4) was the best treatment increasing the average height of bushes to 133 cm and crown diameter to 135 cm. Even in second year its, performance was consistent attaining impressive growth despite the bushes being subjected to 30-40% pruning at the age of 21 months. Total biomass production of A. lentifonnis in T4 treatment was 1830 kg ha-1 as compared to 238 kg ha-1 in control. Water. use efficiency of A, lentiformis increased to 27.2 kg ha-1 cm-1 in T4 from 3.5 kg ha-1 cm-1 in the control.